2021
DOI: 10.1093/restud/rdab089
|View full text |Cite
|
Sign up to set email alerts
|

Caught between Cultures: Unintended Consequences of Improving Opportunity for Immigrant Girls

Abstract: What happens when immigrant girls are given increased opportunities to integrate into the workplace and society, but their parents value more traditional cultural outcomes? We answer this question in the context of a reform which granted automatic birthright citizenship to eligible immigrant children born in Germany after January 1, 2000. Using survey data we collected from students in 57 schools and comparing those born in the months before versus after the reform, we find the introduction of birthright citiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…This may suggest that immigrants also expect more from their daughters when it comes to brokering between them and the host society. On the other hand, Dahl et al (2020) have shown that immigrant Muslim parents in Germany invest less in their daughters' education than sons' and allow sons to take advantage of opportunities while pushing daughters into traditional familial roles. In a quasiexperiment, they show that the discrepancy between opportunities and not being allowed to take advantage of them lowers immigrant girls' well-being and self-esteem more than a simple lack of opportunities.…”
Section: Scholarship On Integration Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…This may suggest that immigrants also expect more from their daughters when it comes to brokering between them and the host society. On the other hand, Dahl et al (2020) have shown that immigrant Muslim parents in Germany invest less in their daughters' education than sons' and allow sons to take advantage of opportunities while pushing daughters into traditional familial roles. In a quasiexperiment, they show that the discrepancy between opportunities and not being allowed to take advantage of them lowers immigrant girls' well-being and self-esteem more than a simple lack of opportunities.…”
Section: Scholarship On Integration Outcomesmentioning
confidence: 99%
“…To sum up, taking into account prior research on household decision-making (Bailey and Boyle 2004;Cooke 2008;Goldring 2001), gendered migration decisions and experiences (Grasmuck and Pessar 1991;Hondagneu-Sotelo 1994;Klüsener et al 2015;Morawska 2011;Pedraza 1991;Striffler 2007;Tummala-Narra 2013), children's role in family migration decisions (Ackers 2000;Bushin 2009;Mason 2000), differential parental investment by offspring sex (Dahl et al 2020;Hopcroft 2005), different levels of risk aversion by offspring sex (Pogrebna, Oswald, and Haig 2018), offspring sex effects on parents' political attitudes (Conley and Rauscher 2013;Warner 1991;Washington 2008), and, finally, boys' and girls' different ability to adapt to new geographical surroundings (Kessler, Duncan, and Gennetian 2014), this paper exploits the randomness of offspring sex to identify the causal effect of having sons or daughters on parents' decision to migrate to Germany, as well as their integration into German society, as measured by their ability to speak German, feeling connected to their neighborhood, and overall life satisfaction.…”
Section: Importance and Contribution Of This Papermentioning
confidence: 99%
See 2 more Smart Citations
“…4 My second contribution to the literature is to propose a revealed preference measure of cultural assimilation, i.e., using hormonal contraceptives. 5 A sense of identity on the part of immigrants (Bisin et al, 2008(Bisin et al, , 2016Dahl et al, 2021) does not provide the full picture of the acculturation process. Someone who grew up in the West may still self-identify as belonging to the country of origin.…”
Section: Introductionmentioning
confidence: 99%